A Influenza espanhola de 1918/1919 na Cidade de Goiás - DAMACENA NETO, Leandro Carvalho (2011)
Research on the Spanish flu in Goiás aimed to understand the impacts and meanings which accounted for the population. We analyze its symptoms Spanish flu, as well as highlight the imprecision of medicine to define and characterize it, the multiple symptoms diagnosed and the variety of treatments and therapeutic measures. For this, the research is anchored in the records of the press Goiás, in the context of 1918/1919 were lodged with the population and called Advice to people: that is, they were indications of health authorities to combat the Spanish flu. More than a biological problem, the Spanish flu became a social problem, and as such has been analyzed here, from its social representation - ie, the disease constituted a problem that requires an explanation by the company attacked, it is imperative that has a social and cultural. Historicize diseases is one of the ways to understand a society.